The study of economics of power generation: article - Sungip, Muhammad Khairil Izwan (Faculty of Electrical Engineering, 2007)
This paper presents a study on operating cost of thermal power generation. The study include Economic Load Dispatch (ELD) concept, in a power system by using MATLAB software package. Comparison in total cost for increases total loss case was made in order to determine the difference on the total generation cost and identify advantage for the total loss minimization. The proposed technique is tested on IEEE 9-bus power system network. Hybrid Optimization Model for Electric Renewables (HOMER) is software used to analyze generation cost of thermal power generation and net present cost (NPC) to choose the best operation system for different fuel which is coal and natural gas either in stand alone application or combined operation. The study identifies how to find minimum cost for this type generation systems and identify the solution to minimize the total loss.